Analysis of the impact of artificial intelligence technologies on reducing costs and increasing the efficiency of resource use in technology development projects in The Kingdom of Saudi Arabia - Mohammed, Anwar Mohammed Qism-Allah (Journal of Economic, Administrative and Legal Sciences, 2025)
The study aimed to identify the impact of artificial intelligence (AI) technologies on reducing costs and increasing the efficiency of resource utilization in technological development projects in the Kingdom of Saudi Arabia. The study population consisted of employees working on technological development projects in Saudi Arabia. The study sample included (97) individuals. The researcher used a descriptive approach and a questionnaire as the study tool. The study reached several conclusions, most notably that there was a significant impact of AI technologies in reducing costs and increasing the efficiency of resource utilization in technological development projects in Saudi Arabia. The first axis, "The impact of AI technologies on reducing costs," received a high response rate with an arithmetic mean of (3.89) and a standard deviation of (0.340). The second axis, "The impact of AI technologies on the efficiency of resource utilization," also received a high response rate with an arithmetic mean (3.70), and a standard deviation (.491). The study recommended several recommendations, including the necessity of holding training courses for employees in technological development projects to qualify them to understand and use AI technologies.
Keywords: Artificial intelligence technologies; cost reduction; increased efficiency of resource utilization